(untitled) (Confluenţe Bibliologice, 2016)
The article refers to the life and creation of Bob Dylan, singer, painter, writer and composer. The 2016 Nobel Prize in Literature was awarded to musician Bob Dylan for creating new poetic expressions within the great American song.His inﬂuence on contemporary music is deep and is the source of inspiration of many books.